2022
DOI: 10.1242/jcs.259187
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic hyperglycemia perturbs the development of specific retinal cell types, including photoreceptors

Abstract: Diabetes is linked to various long-term complications in adults, such as neuropathy, nephropathy, and diabetic retinopathy. Diabetes poses additional risks for pregnant women, because glucose passes across the placenta, and excess maternal glucose can result in diabetic embryopathy. While many studies have examined the teratogenic effects of maternal diabetes on fetal heart development, little is known about the consequences of maternal hyperglycemia on the development of the embryonic retina. To address this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Previous studies demonstrated abnormal retinal development in hyperglycemic zebrafish embryos [ 7 , 8 ]. While the decreased number of photoreceptors, horizontal cells, and ganglion cells corresponded to altered retinal thickness in these embryos, it remained unclear whether the reduced number of retinal cells alone accounted for the observed visual defects or whether there existed any defects in the development of retinal synapses in this model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated abnormal retinal development in hyperglycemic zebrafish embryos [ 7 , 8 ]. While the decreased number of photoreceptors, horizontal cells, and ganglion cells corresponded to altered retinal thickness in these embryos, it remained unclear whether the reduced number of retinal cells alone accounted for the observed visual defects or whether there existed any defects in the development of retinal synapses in this model.…”
Section: Resultsmentioning
confidence: 99%
“…The aquatic zebrafish environment can be manipulated to study the specific effects of a chemical agent on embryo development, which is external, rapid, and easily visualized. For example, immersion of zebrafish in water containing high glucose results in the developmental changes of hyperglycemia [ 7 , 8 ], thereby facilitating our study of these changes. Overall, their relatively easy maintenance, high fecundity, small size, and manipulatable environment make zebrafish an excellent model for vertebrate developmental biology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a major focus on the study of juvenile/adult DR, the effects of hyperglycemia during early retinal development are less well studied. Recent works in embryonic zebra sh models of nutritional hyperglycemia revealed that hyperglycemia leads to decreased cell numbers of mature retinal cell types, which has been related to a modest increase in apoptotic cell death and altered cell differentiation (Singh et al 2019;Titialii-Torres and Morris 2022). However, how embryonic hyperglycemia impacts cell proliferation in developing retinas remains still unknown.…”
mentioning
confidence: 99%